Sequence Analysis of Major Histocompatibility Complex Class-II DQB1 ( Patr-DQB1) Alleles in Chimpanzees by Polymerase Chain Reaction–Based Methods - Bak, EunJung; Ishii, Yoshiyuki; Omatsu, Tsutomu; Kyuwa, Shigeru; Tanoue, Tetsuya; Hayasaka, Ikuo; Yoshikawa, Yasuhiro (Human Immunology, 2006)
The major histocompatibility complex (MHC) class-II genes are described as the genes that encode the antigen-presenting molecule. In particular, functional alleles of MHC class-II genes in nonhuman primates have been analyzed as part of the study of infectious and immune-mediated diseases in animal models and as part of efforts to understand the molecular evolution of human leukocyte antigen. The polymorphisms and sequence analysis of MHC class-II genes in a large number of subjects is necessary for the group management of nonhuman primates. In the present study, we attempted to analyze the DQB1 polymorphism in the common chimpanzee ( Pan troglodytes) by exon 2 sequencing. For exact typing of Patr-DQB1 alleles, we carried out polymerase chain reaction–restriction fragment length polymorphism and sequence analysis. In the genomic DNA of 25 chimpanzees, 6 Patr-DQB1 alleles, including 2 new alleles, were detected. Identification and analysis of Patr-DQB1 alleles using this method may contribute to our understanding of Patr-DQB1 allelic diversity in individual chimpanzees and should be useful in facilitating colony management of chimpanzee groups in Japan.